The Physico-Chemical studies of Khar-e-Khasak (Tribulus terrestris Linn.) - Rasikh Javaid Nengroo,; Raheela Javaid,; Anju Singh,; Ghazala Javed, (International Journal of Phytomedicine, 2020)
Khar-e-Khasak (Tribulus terrestris Linn) commonly known as Gokhru is an important drug of Unani Medicine. It has been described as diuretic, carminative, antiseptic and widely used by Unani Physicians in various gastrointestinal ailments. In this paper studies carried out to determine the ash values, extractive values, fluorescence analysis and thin layer chromatographic parameters are reported which were performed to standardize the fruit of the plant for its purity.